Prevalence and Factors Associated With the Risk of Delayed Sleep-Wake Phase Disorder in Japanese Youth - Tomishima, Sayaka; Komada, Yoko; Tanioka, Kosuke; Okajima, Isa; Inoue, Yuichi (Frontiers in Psychiatry, 2022)
Background: The prevalence of delayed sleep-wake phase disorder (DSWPD) is known to increase in the younger generation. However, the prevalence of this disorder in Asia, particularly Japan, has not yet been elucidated. Furthermore, the impact of DSWPD morbidity on daytime functioning and factors associated with the presence of the disorder remain unclear. Methods: A web-based survey was conducted among youth aged 15–30 years. In total, 7,810 individuals completed the questionnaire. The questionnaire included items on sociodemographic variables as well as the Japanese version of the Biological Rhythms Interview of Assessment in Neuropsychiatry self-report (J-BRIAN-SR), which assesses the presence/absence of DSWPD, sleep behaviors and possibly related lifestyle variables, productivity loss (WHO Health and Work Performance Questionnaire (HPQ)), and health-related quality of life (HRQOL). The presence of DSWPD was defined by a J-BRIAN-SR score greater than or equal to 40 points and days of absence greater than or equal to four days per month. After comparing these variables between participants with and without possible DSWPD, the factors associated with the possibility of DSWPD were examined using logistic regression analysis, with sociodemographic and lifestyle variables as independent variables. Results: The overall prevalence of possible DSWPDs was 4.3%. Compared with participants without DSWPD, those with possible DSPWD presented significantly worse HPQ and HRQOL scores. The presence of possible DSWPD was positively associated with the presence of currently treated diseases, length of nighttime liquid crystal display (LCD) viewing, and high school/university students. It was negatively associated with habitual exercise. Conclusion: The prevalence of possible DSWPD seemed to be compatible with that in Western countries, and individuals possibly affected by the disorder were thought to have deteriorated daytime functioning. In addition, lifestyle specific to youth, such as long-term LCD viewing at night and relatively loose social constraints, could be associated with the presence of DSWPD in this generation.